2021
DOI: 10.1140/epjc/s10052-021-09168-8
|View full text |Cite
|
Sign up to set email alerts
|

Discreteness of space from anisotropic spin–orbit interaction

Abstract: Various approaches to Quantum Gravity suggest an existence of a minimal measurable length. The cost to have such minimal length could be modified uncertainty principle, modified dispersion relation, non-commutative geometry or breaking of continuous Lorentz symmetry. In this paper, we propose that minimal length can be obtained naturally through spin–orbit interaction. We consider Dresselhaus anisotropic spin–orbit interaction as the perturbative Hamiltonian. When applied to a particle, it implies that the spa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For such materials, it has been explicitly demonstrated that the generalized Dirac structure which emerges beyond the linear regime is the GUP deformation of the usual Dirac structure [9]. It is also possible to obtain GUP deformation of the effective theory describing condensed matter systems using spin-orbit interaction [10]. It may be noted that GUP deformation occurs due to an intrinsic minimal length in the system [2,3].…”
mentioning
confidence: 99%
“…For such materials, it has been explicitly demonstrated that the generalized Dirac structure which emerges beyond the linear regime is the GUP deformation of the usual Dirac structure [9]. It is also possible to obtain GUP deformation of the effective theory describing condensed matter systems using spin-orbit interaction [10]. It may be noted that GUP deformation occurs due to an intrinsic minimal length in the system [2,3].…”
mentioning
confidence: 99%
“…On the other hand, this simultaneous reality may be used to explain the instantaneous and non-local correlations when measuring the spin of two entangled particles as we explained above which was set by violation of Bell's inequalities. Possible conceptual connection between minimal length implied by Linear GUP and spin concept was studied in [34].…”
mentioning
confidence: 99%